Evaluation of Patients\' Satisfaction with Health Services Provided in Golestan Hospital, Tehran - F. Pirooz; M. Nuri; M. Goli (Afarand Scholarly Publishing Institute, 2018)
Aims: Patient satisfaction with the services provided during hospitalization is one of the important indices of the quality of health care centers. The aim of this study was to evaluate patientschr('39') satisfaction in Golestan Hospital in Tehran. Instrument and Methods: In this cross sectional, descriptive-analytical study, 426 patients (8 to 96 years old) were selected from patients hospitalized in Golestan Hospital (Tehran) with duration of stay of more than one day, using available sampling method. The study period was one year from April 2016 to March 2017. The questionnaire consisted of two parts: demographic and proprietary information. The standard checklist for patientschr('39') satisfaction from the health system development plan was used to set specific questions. The data were analyzed, by SPSS 16 software, using ANOVA, Chi-square, and independent t-tests. Findings: 73.82% (314 people) of the patients were satisfied with the services provided at the center and 12.65% (54 people) were dissatisfied. The highest satisfaction was in medical services (91.37%) and the lowest was related to food situation (60.55%). The variable of gender did not have significant relationship with satisfaction component (p=0.052), but marital status (p=0.004), level of education (p<0.001) and age (p=0.002) had significant relationship with satisfaction component. Conclusion: Marital status, level of educational and age are related to the degree of satisfaction of hospitalized patients, but gender is not related to satisfaction.